Pengaruh Pemupukan terhadap Pertumbuhan, Hasil dan Kualitas Biji Empat Klon Kopi Robusta di Tanah Podsolik Merah Kuning, Lampung Utara - Rusli Rusli; Sakiroh Sakiroh; Edi Wardiana (Pusat Penelitian dan Pengembangan Perkebunan, 2015)
Recommendation of Robusta coffee fertilizer that available until now is only in general. In fact, the type and amount of fertilizer needed is highly dependent on environmental conditions, clones, and plant age. The study aimed to investigate the effect of combination doses of urea, SP36, and KCl fertilizer on growth, yield, and bean quality of four Robusta coffee clones cultivated in red-yellow podzolic soil type (PMK), North Lampung. The study was conducted at KP. Cahaya Negeri, North Lampung, with the altitude of 250 m above sea level, PMK soil type and climate type of C (Oldemand), from October 2011 to June 2014. The research was arranged in split plot design with four replications. The main plot was four Robusta coffee clones i.e. (K1) = BP 42; (K2) = BP 409; (K3) = BP 936; and (K4) = BP 939, while the subplot was four combination doses of urea, SP36, and KCl i.e. (P1) = 30:20:20 g/tree; (P2) = 40:30:30 g/tree; (P3) = 50:40:40 g/tree; and (P4) = 60:50:50 g/tree. The results showed that four Robusta coffee clones (BP 42, BP 409, BP 936, and BP 939) cultivated in PMK soil type, KP. Cahaya Negeri, North Lampung, had the same response to combination doses of urea, SP36 and KCl fertilizer. The combination doses of urea, SP36, and KCl of 50, 40, and 40 g/tree, respectively were optimal and efficient for growth and yield of those four clones until 2.5 years old. However, the dose has not yet been able to improve the quality of coffee beans.